FAKTOR – FAKTOR PERENCANAAN PAKET WISATA DI PT.BONANZA PEKANBARU HOLIDAY - Yuliawati, Heny; Arief, Andi M Rifiyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was conducted to determine how the planning of tour packages in PT.Bonanza Pekanbaru Holiday and what kind of consumer response to travel package in PT.Bonanza Pekanbaru Holiday.This study used a qualitative descriptive method for analyzing the problems. Key informant in this study is the first person from the management is Managing Director at PT.Bonanza Pekanbaru Holiday and 31 customers who come in and use the tour package designed by PT.Bonanza Pekanbaru Holiday. Key Informant determination in this study using purposive sampling technique and for the determination of informants from the customer using accidental sampling technique, where the data collection techniques used is by observation, interview and documentation. Theory in this research is processed authors of the factors of packages tour planning the book Tours and Travel Marketing (Oka A. Yoeti, 2006).Results of this study are expected to improve the planning of tour packages and travel packages to increase sales, especially for PT.Bonanza Pekanbaru Holiday and the entire business travel services providers in Riau.Keywords : Packages tour, Factors of Packages Tour Planning